2018
DOI: 10.1080/03088839.2018.1516049
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based severe weather-induced container terminal economic loss estimation

Abstract: It incorporates referee's comments but changes resulting from the publishing process, such as copyediting, structural formatting, may not be reflected in this document. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Interestingly, an increase in wind-induced port disruptions is reported, while disruptions associated with storm surges have decreased. Cao and Lam (2019) assess weather-induced port disruptions between 2013 and 2017 for the Port of Shenzhen, finding a total number of 170 weather events that caused downtime. The authors find that the month March has an average monthly downtime of seven days between 2013 and 2017, mainly associated with fog, whereas the months of July and August have an average monthly downtime of around four days due to typhoons and rain.…”
Section: Empirical Evidence Port Disruptionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, an increase in wind-induced port disruptions is reported, while disruptions associated with storm surges have decreased. Cao and Lam (2019) assess weather-induced port disruptions between 2013 and 2017 for the Port of Shenzhen, finding a total number of 170 weather events that caused downtime. The authors find that the month March has an average monthly downtime of seven days between 2013 and 2017, mainly associated with fog, whereas the months of July and August have an average monthly downtime of around four days due to typhoons and rain.…”
Section: Empirical Evidence Port Disruptionsmentioning
confidence: 99%
“…port-level, regional-level, national-level). Port-level approaches either use hydrodynamic or weather-simulating models in combination with operational thresholds of ports (Camus et al, 2019;Esteban et al, 2016;Sierra et al, 2017;Zhang and Lam, 2015) or a simulation model of the port functioning in order to estimate the economic losses of downtime for a port (Cao and Lam, 2019;Zhang and Lam, 2016). The abovementioned studies rely on a relationship between the event (e.g.…”
Section: Impact Modelling Port Disruptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it appears that maritime operations are highly susceptible to disruptions. Firstly, some researches have shown that natural disaster made great impact to maritime business as it generated the highest impact due to disruption events such as economic loss and downtime (Lam & Su, 2015;Lam & Lassa, 2017;Cao, 2019). Another findings are operational risk like equipment breakdown or failure and shortage of facilities may are the key factors in causing great disruptions in maritime operations (Loh et al, 2017).…”
Section: Business Continuity Management In Maritime Operationsmentioning
confidence: 99%